Content and Face Validity of An Instrument to Measure the Practice of Inpatient Nurses in Preventing Patient from Falling - Andi Baso Tombong; Yuliana Syam; Ani Auli Ilmi; Rismayanti Waris; Andi Nur Inayah; Amanah Restuyana; Selviani Rahmasari; Muh. Gunawan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Fall incidence among healthcare facility patients has recently become a patient safety issue. To date, instruments to measure nurses’ performance in preventing patient fall incidence have been lacking. This paper aims to report the first and the second phases of an instrument to measure the implementation of patient fall prevention by nurses working in hospitals’ inpatient units or wards. The instrument, Self-Reported Questionnaire: Implementation of Nurses in Inpatient Wards in Preventing Fall among Patients (INI-PFP), was developed using the scale development method. In the first phase, domain and item generation was identified, followed by content validity (panel of 11 experts from universities and hospitals) and readability test/ face validity of 14 inpatient nurses). The study initially generated 46 items from the instrument development process. The initial instrument was sent to 11 experts, assessing the items’ relevance, clarity, simplicity, and ambiguity. This stage reduced three items, with the remaining items’ S-CVI = 0.99 for the four categories. The 43 items were subsequently provided to 14 inpatient nurses from four hospitals in the readability test and face validity with 98,17% of the items’ clear instructions, ranging from 57%-100% of question agreement. From this stage, 13 items were re-written and brought to a second round of face validity involving eight nurses from two hospitals. The end of the face validity test considered the 43-Items INI-PFP were adequate to enter the final phase, including Construct Validity and the Psychometric Evaluation for its final validity and reliability.